Evolución de la inclusión financiera del sistema financiero en la región Loreto, periodo 2013-2022 - Saquiray Bocanegra, Susan Masiel (2024)
The study analyzes the evolution of Financial Inclusion in the Loreto Region during the period 2013-2022, with the objective of identifying the behavior of access, use, and depth of financial services in the region. The methodology was carried out through a non-experimental and descriptive-longitudinal design, using document observation techniques to collect data from the Superintendence of Banking, Insurance, and AFP (SBS) and the National Institute of Statistics and Informatics (INEI), which were processed and analyzed using Excel and descriptive statistical techniques. The results show that access to and use of financial services increased, indicating greater availability and utilization of services such as bank accounts and loans in the region. The depth of financial inclusion, measured through indicators such as the credit/GDP and deposit/GDP ratios, also showed a positive trend, although with fluctuations in some years. It is concluded that financial inclusion has improved in Loreto, contributing to the economic development of the region, but challenges remain regarding equitable access, coverage, and effective use of these services, particularly in rural areas. This study provides valuable evidence for the design of public policies aimed at improving financial inclusion in regions with similar characteristics.